Microbiome-induced antigen-presenting cell recruitment coordinates skin and lung allergic inflammation - Ubags, Niki D.; Trompette, Aurélien; Pernot, Julie; Nibbering, Britt; Wong, Nicholas C.; Pattaroni, Céline; Rapin, Alexis; Nicod, Laurent P.; Harris, Nicola L.; Marsland, Benjamin J. (Journal of allergy and clinical immunology, 2021)
Allergic skin inflammation often presents in early childhood; however, little is known about the events leading to its initiation and whether it is transient or long-term in nature. We sought to determine the immunologic rules that govern skin inflammation in early life. Neonatal and adult mice were epicutaneously sensitized with allergen followed by airway allergen challenge. Epicutaneous application of labeled allergen allowed for determination of antigen uptake and processing by antigen-presenting cells. RNAseq and microbiome analysis was performed on skin from neonatal and adult specific pathogen-free and germ-free mice. A mixed TH2/TH17 inflammatory response in the skin and the lungs of adult mice was observed following sensitization and challenge. Comparatively, neonatal mice did not develop overt skin inflammation, but exhibited systemic release of IL-17a and a TH2-dominated lung response. Mechanical skin barrier disruption was not sufficient to drive allergic skin inflammation, although it did promote systemic immune priming. Skin of neonatal mice and adult germ-free mice was seeded with low numbers of antigen-presenting cells and impaired chemokine and alarmin production. Enhanced chemokine and alarmin production, and seeding of the skin with antigen-presenting cells capable of instructing recruited cells to elicit their effector function, was, at least in part, dependent on formation of the microbiome, and consequently contributed to the development of overt skin disease. These data shed light on the principles that underlie allergic inflammation in different tissues and highlight a window of opportunity that might exist for early-life prevention of allergic diseases. [Display omitted]